Historical trip to puncak Penulisan temple, a journey to discover ancient civilization of Bali Kuna Empire - I Gede Mas Suputra (Bali Tourism Board, 2019)
Beyond thick fog and ensnaring freeze of Penulisan hill, there is situated an ancient history. A temple that endured since far before the ruling of Bedahulu Dynasty dated back in the eighth century. The old site acts as a religious center, known by local as Puncak Penulisan Temple. It is located on the highest spot of Bangli regency. Puncak Penulisan temple is a temple complex, in a site resembles a seven level terraces pyramid. In ancient Balinese Kingdom period, between 882 – 1436 AD, the community sanctified several temples, including Puncak Penulisan temple as a place to worship the spirit of ancestor as well as their ruler. Discovered artifacts from this ancient site encompass varies type of megalithic artifacts such as a stone carved with moon and sun image, a statue of Brahma, three pairs statues, two Lingga-Yoni as a symbol of Lord Shiva, Ganesha figure, and several mini rock shrine to worship the holy spirit. unlike other regions in Bali, in Puncak Penulisan temple, the ritual is led by a priest called Jero Kubayan. Furthermore, in every ceremony that takes place in the temple, is taking care by a group of people called Gebog domas. A group of people consists of 200 family heads from Sukawana, Kintamani, Selulung, and Bantang regions, bringing a total of 800 people. Gebog Domas played an essential role as a symbol of unity between villages as well as to strengthen the brotherhood.